Easy353: A Tool to Get Angiosperms353 Genes for Phylogenomic Research. (2nd December 2022) - Zhang, Zhen; Xie, Pulin; Guo, Yongling; Zhou, Wenbin; Liu, Enyan; Yu, Yan
Abstract: The Angiosperms353 gene set (AGS) consists of a set of 353 universal low-copy nuclear genes that were selected by examining more than 600 angiosperm species. These genes can be used for phylogenetic studies and population genetics at multiple taxonomic scales. However, current pipelines are not able to recover Angiosperms353 genes efficiently and accurately from high-throughput sequences. Here, we developed Easy353, a reference-guided assembly tool to recover the AGS from high-throughput sequencing (HTS) data (including genome skimming, RNA-seq, and target enrichment). Easy353 is an open-source user-friendly assembler for diverse types of high-throughput data. It has a graphical user interface and a command-line interface that is compatible with all widely-used computer systems. Evaluations, based on both simulated and empirical data, suggest that Easy353 yields low rates of assembly errors.